Membumikan Deradikalisasi Pendidikan Islam sebagai Respons Antisipatif Radikalisme di Era Global - Andik Wahyun Muqoyyidin (Proceedings of Annual Conference for Muslim Scholars, 2017)
This paper aims to describe the systematic and holistic efforts to unearth the de-radicalization of Islamic education. The rise of radicalism in the name of religion on the global stage, particularly in Indonesia, both with an old and new-style format, demanding the authorities to seriously think of a proper strategy for overcoming it. All rightly appreciate the government’s determination to continue to optimize the de-radicalization program in order to ward off misunderstandings and extreme ideology. Although the roots of the rise of radicalism among Muslims, it is complex, but in fact indirectly it reflects an Islamic education learning practices that have been implemented at various levels of education. One of the major breakthroughs related to rejuvenating this de-radicalization program can be started from the reorientation of the Indonesian Islamic education vision towards strengthening inclusive vision-multiculturalist. That is, early on, some important components of Islamic education, as components of the curriculum, educators, and learning strategies should be directed to equip learners life skills (soft skills) face various challenges they will encounter in the midst of social life are very diverse (plural), both in terms of religion and belief (multireligious), language (multilingual), race, ethnicity (multiethnic), as well as the traditions and cultures (multicultural).Keywords: De-radicalization; Islamic education; Radicalism; Global.